Perilaku Komunikasi dan Kinerja Penyuluh Pertanian pada Era Digital di Kecamatan Tilongkabila - Anwar Fendy; Yuliana Bakari; Yanti Saleh (Jurnal Sosial Ekonomi Pertanian, 2021)
This study aims: 1) to determine the individual characteristics of agricultural instructors in the digital era in Tilongkabila District, 2) to analyze the communication behavior and performance of agricultural extension agents in the digital era in Tilongkabila District. This research was conducted at the BP3K office, Tilongkabila District, Bone Bolango Regency, with a total sample of 13 extension workers. The research method used is a survey method. The data analysis used in this research is quantitative descriptive with percentage formula and job performance value descriptive. The results showed that 1) the characteristics of the extension workers in Tilongkabila District were dominated by women with undergraduate education levels aged 35 to 46 years and most of them were THL extension workers who had a working period of 11-20 years, where most of the extension workers already had communication media in the form of telephone smart (smartphone) to support the implementation of their duties in the field. 2) the communication behavior in this study has a percentage of 33.04% which indicates that the instructor is still not good at communication behavior. Furthermore, the overall performance value of the instructor's performance with the total number obtained was 63.31% or it can be said that the performance of the instructors in Tilongkabila District went quite well.